THE RELATIONSHIP OF NUTRITIONAL KNOWLEDGE AND BODY IMAGE PERCEPTION WITH NUTRITIONAL STATUS AMONG ADOLESCENT GIRLS AT SMA NEGERI 5 KENDARI - Putri Awalnda Pratiwi; Febriana Muchtar; Paridah Paridah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
Nutritional status among adolescent girls is an important indicator of health, growth, and development. Nutritional knowledge and body image perception are considered factors associated with nutritional status; however, previous studies have reported inconsistent findings. This study aimed to analyze the relationship between nutritional knowledge and body image perception with the nutritional status of adolescent girls at SMA Negeri 5 Kendari. This study employed a quantitative analytical observational design with a cross-sectional approach. The study population consisted of 517 female students in grades X and XI, with a sample of 249 respondents selected using a stratified random sampling technique. Data on nutritional knowledge were collected using a structured questionnaire, body image perception was assessed using the Body Shape Questionnaire (BSQ), and nutritional status was determined based on Body Mass Index-for-Age (BMI-for-Age). The Chi-square test indicated no significant relationship between nutritional knowledge and nutritional status (p = 0.116) or between body image perception and nutritional status (p = 0.062). It can be concluded that nutritional knowledge and body image perception were not significantly associated with the nutritional status of adolescent girls at SMA Negeri 5 Kendari. Therefore, efforts to improve adolescents' nutritional status should also consider other contributing factors, such as dietary habits, physical activity, socioeconomic conditions, and family support.